Analisis Strategi Marketing Mix Untuk Meningkatkan Volume Penjualan Pada Nissan Datsun Cabang Magelang - Finda Tiyas (Universitas Nusa Putra, 2021)
Marketing strategy is an important factor in the development of the company and can increase sales volume. This study aims to determine the strategies used by Nissan Datsun Magelang branch dealers and the influence of the staristics used on sales volume. This research is a qualitative research using interview data collection techniques, literature study, observation and documentation directly at the Nissan Datsun Magelang branch dealer. The results showed that the marketing strategy applied by the Nissan Datsun Magelang branch was a marketing mix marketing mix strategy which consisted of (Product, Price, Places, Promotion).